Development of handling and transport protocols for Eldana saccharina (Lepidoptera: Pyralidae) sterile insect technique (SIT) programme - Serfontein, Adriaan Jacobus (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScConsEcol)--Stellenbosch University, 2021.